Small Metropolitan Areas in Rapid Transition: The Case of Patras - Vassilis Pappas (European Regional Science Association (ERSA), 2006)
Patras is the third urban complex in Greece, concerning the population size, sited in the North-West Pelopennese and one of the oldest ones, having a continuous history of 4.000 years. The modern history of city of Patras is characterized by a rapid and continuous development and transformation, concerning its structure, function and its physiognomy. This fact is documented by studying a lot of facts and figures, but mainly from a simple reading of its spatial evolution, characteristics and changes. Although Patras is the first city having an official Master Plan, in modern Greece (since 1827), its historical route and evolution is far from a rational and planned one. On the contrary, and as the typical Greek model of cities' development is, it follows an absolutely non-rational, non-planned model, that does not secure the quality of living and mainly does not form a visual and sustainable development aim in the European or, at least, in the Greek context. The city – whatever that means – seems to be unready to face these challenges and does not have the proper infrastructure and planning framework to be able and conscious to form its own development route. No matter how it sounds, the city is a simple viewer of its own restructure and transformation route. The strategic planning alternatives are missing or are absolutely insufficient. The planning process is limited to fragmentary studies, actions, activities and/or initiatives. This work presents and analyses Patras` main characteristics, its evolution, the limitations and problems, in planning process, and forms and documents a proposal concerning a modern planning framework based on a social controlled planning conservancy.
Keywords: 330